MAKNA GRAMATIKAL KEREDOMO, DEMO, SHIKASHI DALAM CERITA PENDEK SHIRO KARYAAKUTAGAWA RYUNOSUKE - Yusi Sofia Rini; Diah Soelistyowati (LITE: Jurnal Bahasa, Sastra, dan Budaya, 2016)
This examined about the Grammatical meaning of setsuzokushi keredomo, demo and shikashi in a short story titledâ€œShiroâ€ by Akutagawa Ryunosuke. The purpose of this researchis to examine the functions of setsuzokushi keredomo, demo and shikashi in ashort story titledâ€œShiroâ€. The author used descriptive analysis method in qualitative paradigm. The authorâ€™s ability to assert this research in terms based on existed data and analyze based on reasons was the priority in the process of writing this research. The result of this research showed the functional variety of gyakusetsu setsuzokushi keredomo, demo and shikashi, but both of setsuzokushi keredomo, demo and shikashi have the same meaning which is use to express opposite things.Keywords: Grammatical meaning,keredomo, demo, shikashi,gyakusetsu setsuzokushi